Analisis Data Kecepatan Angin di Pulau Jawa Menggunakan Distribusi Weibull - Atika Ratna Dewi; Sri Handini (Program Studi Statistika FMIPA UNJ, 2022)
Wind is one of the renewable energy products that is environmentally friendly and has a great opportunity as a source of meeting the energy needs of the world's population. In the use of wind as renewable energy, research must be carried out first to determine wind conditions in an area and the method that can be used is the Weibull distribution. In this journal, what will be discussed is the analysis of wind speed data on the island of Java using the Weibull distribution. From the results of the analysis, the wind speed results by province are as follows, Banten Province 2 m/s with a probability of 65%, DKI Jakarta 3 m/s with a probability of 30%, West Java 3 m/s with a probability of 90%, Central Java 8 m/s s with a probability of 11%, East Java 7 m/s with a probability of 7%, DI Yogyakarta is less than 1 m/s with a probability of 98%. The results of the plot of the probability solid function of the Weibull distribution show that the shape of the provincial velocity data curve that corresponds to the Weibull distribution curve is only the curve of East Java Province with a value of 1 < k < 2, namely k = 1.74.